2014
DOI: 10.3109/17453674.2014.922730
|View full text |Cite
|
Sign up to set email alerts
|

Metal release and metal allergy after total hip replacement with resurfacing versus conventional hybrid prosthesis

Abstract: BackgroundMetal-on-metal (MOM) total hip arthroplasties were reintroduced because of the problems with osteolysis and aseptic loosening related to polyethylene wear of early metal-on-polyethylene (MOP) arthroplasties. The volumetric wear rate has been greatly reduced with MOM arthroplasties; however, because of nano-size wear particles, the absolute number has been greatly increased. Thus, a source of metal ion exposure with the potential to sensitize patients is present. We hypothesized that higher amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…The effect of Co 2+ and Cr 3+ ions on osteoclast formation and resorption activity is in the focus of interest, since both ions are applied in prosthetic implant alloys. Co 2+ and Cr 3+ are released from wear particles after metal-on-metal joint arthroplasty and the concentration of these ions is elevated in serum and urine of the respective patients [ 10 , 11 ]. It was shown, that metallic wear particles from cobalt-chromium alloys induce the formation of multinucleated giant cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of Co 2+ and Cr 3+ ions on osteoclast formation and resorption activity is in the focus of interest, since both ions are applied in prosthetic implant alloys. Co 2+ and Cr 3+ are released from wear particles after metal-on-metal joint arthroplasty and the concentration of these ions is elevated in serum and urine of the respective patients [ 10 , 11 ]. It was shown, that metallic wear particles from cobalt-chromium alloys induce the formation of multinucleated giant cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-on-metal articulations recently had a revival and began to replace metalon-polyethylene articulations, which are susceptible to osteolysis and early aseptic loosening. 38,39 However, although metalon-metal articulations reduce volumetric wear (the debris generated during the wear of a bearing over the entire surface area of contact), corrosion can still occur at metal-on-metal junctions and metal ions can be released. In fact, there is evidence that the absolute number of wear particles has actually increased due to the minute size of metal wear particles.…”
Section: Reaction To Metal Ionsmentioning
confidence: 99%
“…Various other studies have found that there is no increase in metal allergies following the implantation of a metal-on-metal articulation, and existing metal allergies do not result in implant complication. 38,95 Thienpont and Berger 96 even noted that a patient with serious metal allergies to chromium, cobalt, and nickel received a hip implant made of cobalt-chromium alloy and had no symptoms of metal hypersensitivity.…”
Section: Reaction To Metal Ionsmentioning
confidence: 99%
“…La diminution physiologique de la clairance rénale à partir d'un certain âge, pourrait de même expliquer les taux sanguins de cobalt élevés observés chez des patients âgés porteurs d'une PHM [22]. D'après une étude récente sur les allergies aux métaux chez des patients porteurs de prothèse depuis 5 ans, la prévalence de ces hypersensibilités chez les porteurs de PHMM n'est pas différente de celle observée chez les porteurs de prothèse de hanche à couple métal-polyéthylène [28]. Néanmoins, en raison du principe de précaution, les prothèses métalliques sont à éviter chez les insuffisants rénaux, ainsi que chez les femmes en âge de procréer et chez les patients allergiques aux métaux [19].…”
Section: Synthèse Revuesunclassified